Combined Therapy of Arterial Hypertension. The Opinion of a Clinical Pharmacologist - M. V. Zhuravleva; E. V. Luchinina; T. V. Shelekhova; S. Yu. Serebrova; S. A. Belkov; A. I. Dmitriev; G. I. Gorodetskaya (Рациональная фармакотерапия в кардиологии)
Modern tactics of treatment of arterial hypertension (AH) involves the use of both monotherapy and combination therapy. Monotherapy is recommended primarily for low-risk patients with systolic blood pressure (BP)< 150 mm Hg. Monotherapy should also be preferred in very high risk patients with high normal BP and frail elderly patients. However, combination therapy is recommended for most hypertensive patients as initial therapy. Starting combination therapy is more effective in lowering BP than monotherapy. Even at low doses, it is usually more effective than maximum dose monotherapy. The most commonly prescribed combinations today contain a renin-angiotensin system blocker (angiotensin converting enzyme inhibitors or angiotensin II receptor blocker) with a calcium antagonist or diuretic. The combination of lisinopril with amlodipine not only proved its high efficiency in various international and Russian studies, but also turned out to be pharmacoeconomically more profitable. Fixed combinations of lisinopril and amlodipine are the optimal choice in the treatment of hypertensive patients, due to all the advantages of both components: higher efficacy and safety rates compared to monotherapy and better patient adherence to treatment.